ChemInform Abstract: Solid State Synthesis, Characterization, Optical Properties and Cooperative Catalytic Performance of Bismuth Vanadate Nanocatalyst for Biginelli Reactions. Issue 31 (August 2015) - Khademinia, Shahin; Behzad, Mahdi; Jahromi, Hamideh Samari
Abstract The new nanocatalyst shows excellent catalytic efficiency in the Biginelli reaction under solvent‐free conditions.